The Impact of Changes in Local Food Consumption of Sweet Potato and Sago into Rice Food, in Kampung Makimi, Makimi District, Nabire Regency, Papua Province - BARANSANO, ROSDIANA; WINDIA, I WAYAN; SUARDI, I DEWA PUTU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019, 2019)
The Impact of Changes in Local Food Consumption of Sweet Potato and Sago into Rice Food, in Kampung Makimi, Makimi District, Nabire Regency, Papua Province The impact of rice policy is a change in the pattern of local food consumption of the community. This study aims to determine the impact of changes in the pattern of consumption of sweet potato and sago local food into rice food consumption. The sampling method uses simple random sampling as many as 40 household headsfrom 402 populations, theanalysis method used in this study is qualitative descriptive. The results showedthe impact of changes in the pattern of consumption of local food of sweet potatoes and sago into rice consumption was a massive shift in public consumption resulted in a decrease in the level of preference for local sweet potato and sago food consumption. Most households prefer to consume rice food, because it tastes good and is easily accessible. This can be seen by the amount of rice consumption as much as 1,443.8 kg / year, while the amount of sweet potato consumption is 182.4 kg / year, and sago is 728 kg / year. The negative impact of government policies and programs on rice food availability has resulted in reduced production of local sweet potatoes and sago. So the price of sweet potatoes and sago became expensive. Changes in the pattern of consumption of local foods of sweet potatoes and sago into rice resulted in an increase of 18.75% in Diabetes Meliatus in Makimi Makimi Village. Suggestion that can be submitted as input is that necessary to process local food into value-added commodities that can attract households to consume local food. The government is expected to formulate regulations related to the food sovereignty program, especially local sweet potatoes and sago. Government policies for the assistance of raskin should be reduced by quota, and replaced by a food subsidies program based on local food. There needs to be a tithe regarding the diversification of consumption of nutritiousbalanced food, especially in utilizing local food potential.